Simpanan deposito mudharabah dan tingkat bagi hasil Deposito berpengaruh pada kinerja keuangan bank syariah - Tiastiti, Septianing (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
This study aims to determine the effect of mudharabah deposit deposits and deposit profit sharing rates on financial performance at Islamic commercial banks. This study uses secondary data sources in the form of quarterly financial bank documentation of Islamic commercial banks. The results of the study based on the t-test or partially show that mudharabah deposits have a positive and significant effect on the financial performance of sharia commercial banks and the deposit sharing rate has a positive and no significant impact on financial performance. Simultaneously (F test) shows that mudharabah deposit and deposit sharing rates have a positive and significant effect on financial performance.